Treat and Extend Regimen of Aflibercept in the Treatment of Type 1 Choroidal Neovascularization Secondary to Chronic Central Serous Chorioretinopathy: Three-year Follow-Up - Kustryn TB; Zadorozhnyy OS; Nasinnyk IO; Nevska AO; Troianovska KV; Pasyechnikova NV; Korol AR (Clinical Ophthalmology, 2025)
Taras B Kustryn, Oleg S Zadorozhnyy, Illia O Nasinnyk, Alla O Nevska, Kseniia V Troianovska, Nataliya V Pasyechnikova, Andrii R Korol Laser Microsurgery Department, The Filatov Institute of Eye Diseases and Tissue Therapy of the National Academy of Medical Sciences of Ukraine, Odesa, UkraineCorrespondence: Taras B Kustryn, Laser Microsurgery Department, The Filatov Institute of Eye Diseases and Tissue Therapy of the National Academy of Medical Sciences of Ukraine, Frantsuzkyi Boulevard 49/51, Odesa, 65061, Ukraine, Tel +380679735343, Email tkustryn@gmail.comPurpose: To report three-year treatment results of intravitreal aflibercept using a treat-and-extend (TAE) regimen for type 1 choroidal neovascularization (CNV) in chronic central serous chorioretinopathy (CSC).Patients and Methods: This prospective, single-center interventional study completed 34 patients (34 eyes) (16 patients previously treated by photodynamic therapy (PDT) and 18 naive patients) treated with 2.0 mg intravitreal aflibercept. All patients received 3 initial loading intravitreal injections every 4 weeks, followed by a TAE protocol. The primary outcome was decimal best-corrected visual acuity (BCVA) at year 3.Results: Overall, mean decimal BCVA increased significantly from 0.44 (SD; 0.35) at baseline to 0.59 (SD; 0.31) at the final visit (p˂0.001). At year 3, mean decimal BCVA in the PDT-treated group compared to the naive group was statistically different, 0.48 (SD; 0.29) vs 0.71 (SD; 0.31), respectively (p=0.04). Overall, complete resolution of fluid was noted in 73% at 3 years. Complete resolution of fluid in the PDT-treated group and the naive group was 56% and 89% (p=0.01), respectively. The total mean number of aflibercept injections was 18.0 (SD; 5.6). Mean number of injections was 20.1 (SD; 5.3) in the PDT-treated group and 15.9 (SD; 5.8) in the naive group (p=0.03).Conclusion: Intravitreal aflibercept using a TAE regimen improved visual and anatomical outcomes of patients with type 1 CNV secondary to chronic CSC in long-term follow-up. Naive patients had a better visual outcome and a higher incidence of complete fluid resolution than PDT-treated patients.Keywords: chronic central serous chorioretinopathy, choroidal neovascularization, anti-vascular endothelial growth factor, aflibercept, treat-and-extend regimen